Hepatic steatosis and fibrosis in chronic inflammatory bowel disease - Veltkamp, Claudia; Lan, Shuai; Korompoki, Eleni; Weiss, Karl-Heinz; Schmidt, Hartmut; Seitz, Helmut K. (Journal of Clinical Medicine, 2022)
Background and Purpose: Chronic inflammatory bowel diseases (IBD) frequently affect extraintestinal organs including the liver. Since limited evidence suggests the presence of liver disease in IBD patients, we studied the frequency of hepatic steatosis and fibrosis in these patients and characterized disease-related factors. Methods: In this retrospective, cross-sectional, hospital-based, single-center study, consecutive patients with Crohn’s disease (CD) and ulcerative colitis (UC) were included who had undergone routine abdominal ultrasound including transhepatic elastography. Hepatic steatosis was diagnosed by hyperechogenicity on B-mode ultrasound and by measuring controlled attenuation parameter (CAP). Hepatic fibrosis was assumed if transhepatic elastography yielded a stiffness > 7 kPa. Results: 132 patients (60% CD) with a median disease duration of 10 years were included. Steatosis assessed by B-mode ultrasound and CAP correlated well. Of the IBD patients, 30.3% had non-alcoholic fatty liver (NAFL). Factors associated with NAFL were age, BMI, duration of disease, as well as serum activities of aspartate-aminotransferase (AST) and gamma-glutamyl-transpeptidase (GGT). In multivariate analysis, only disease duration was independently associated with hepatic steatosis. Hepatic fibrosis was found in 10 (8%) of all IBD patients, predominantly in patients with CD (10/11). Conclusions: Pure hepatic steatosis is common in both CD and UC, whereas hepatic fibrosis occurs predominantly in CD patients. Association of disease duration with NAFLD suggests a contribution of IBD-related pathogenetic factors. Longitudinal studies are needed to better understand the impact of IBD on hepatic disorders.
Gesehen am 23.06.2022
This article belongs to the Topic Liver Fibrosis and Cirrhosis